PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V SDN 029 TELUK ERONG KECAMATAN RENGAT - Efniwaty '; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research is based on the fact that happened in class V SDN 029 Teluk Erong Kecamatan Rengat, which indicates a low reading skills of students. The problem of this research is